Professional Barriers in the Future Teachers' Readiness to Work at Inclusive Schools - I. A. Rudneva; O. A. Kozyreva (Высшее образование в России)
Nowadays there is a lack of empirical data demonstrating the degree of professional barriers in the future teachers` readiness to work at inclusive schools. This problem is relevant for the training teachers at universities. The purpose of this article is to present the results of the study of qualitative and quantitative characteristics of professional barriers that arise among future teachers in the process of preparing for working at inclusive schools, the results of the testing the pedagogical technology to overcome professional barriers in training future teachers. The study involves 393 students majoring in specialty “Pedagogical education”. The authors use the questionnaire called “Professional barriers in the future teachers` readiness to work at inclusive schools”. The research found the imperfection of professional training for the implementation of inclusive education. There are academic, activity, social, personal, resource professional barriers that arise among future teachers in preparing for working at inclusive schools. Professional barriers are caused by some deficits. They do not allow future teachers to perform their professional and pedagogical activities at an acceptable quality level. The classification of professional barriers based on the analysis of empirical data is presented. The content and features are described. The systematization of empirical data made it possible to develop a pedagogical technology to overcome professional barriers in training future teachers at the university. The approbation of pedagogical technology contributes to clarifying scientific ideas about the process of professional and personal formation of future teachers in terms of identifying and overcoming their professional barriers. The results of the study may be used in training students majoring in specialty “Pedagogical education”. Professional barriers are considered to be a significant aspect of the professional teaching training.